Assessing the Effect of Lean Techniques on Construction Projects Performance - ELORABY, SHEHABEDDIEN (İstanbul Kültür Üniversitesi, 2024)
Inefficiency and waste permeate the construction industry, manifesting as extended timelines, inflated costs, and suboptimal resource utilization. Lean construction principles, however, offer a promising paradigm shift, enabling process streamlining and enhanced productivity. This research delves into a crucial question: to what extent can lean tools demonstrably improve construction efficiency, productivity, and performance compared to traditional methods? By adopting a rigorous simulation modeling approach, this study utilizes Discrete Event Simulation Approach to develop comprehensive models encompassing both baseline (conventional) and lean scenarios. By meticulously comparing these models, statistically significant insights were generated into the effectiveness of integrating lean techniques. The findings provide compelling evidence for the transformative power of Lean in improving project outcomes. Applying key principles like value specification, value stream mapping, value flow, pull production, and continuous improvement resulted in significant performance gains, while optimizing process and operational aspects further reduced project total time, solidifying the benefits of a leaner approach. Lean models demonstrated a 7.79% increase in process efficiency and a 30.29% reduction in cycle time for the retaining wall construction process, Moreover, the research transcends mere potential demonstration by quantifying the measurable impact of implementing specific lean tools, providing construction practitioners with clear evidence of their effectiveness, and developing practical guidelines for seamlessly integrating lean thinking into established management approaches, bridging the gap between theory and practice.
Yalın Tekniklerin İnşaat Projeleri Performansına Etkisinin Değerlendirilmesi
Yüksek lisans tezi.
Keywords: Waste Reduction; Performance Development